Characterization and product indentification of sludge obtained from the recycling of lubricant into base oil - Thavasigamani, Loshbinan (2008)
This study describes the characterization and product identification of sludge that is obtained from the recycling of spent lubricant into base oil. Sludge is produced from the recuperation of spent lubricant which involves two main processes. The first process is to produce the solvent that will be used. The solvent consists of Hexane, Isopropanol (IPA) and Potassium hydroxide (KOH). The next process is the recuperation of used lubricant using the solvent produced. The ratio of spent lubricant and solvent used is 1:4. Physical mixing is then used to produce a natural reaction between the solvent and spent lubricant. The mixture is stirred continuously for 30 minutes. The stirred mixture is then filtered. There are two ways to filter the mixture. One is by centrifugation and the other is filtration with thin filter papers. The residue that is left behind is the sludge that is going to be used for the characterization process. Many parameters of the sludge is investigated and characterized before product identification is done. Both physical and chemical parameters are investigated. The parameters investigated are pH, density, viscosity, heavy metal content and chemical composition of the sludge. The pH of sludge on average is 6.59 with an average density of 0.9041 g/ml or 904.13 kg/m3. The average viscosity is 1419 cP. There is a fair amount of heavy metals present in the sludge and its chemical composition consists of paraffin and olefins. From the results obtained, the sludge can be singled out for its major components and the contents can be derived into useful products. Three different products are identified. The sludge can be used as raw material for pyrolysis where the end product obtained is a diesel like liquid and also as concrete or cement additive. The sludge can also be used as grease.